Comparative Quality of Laparoscopic and Open Cholecystectomy in the Elderly Using Propensity Score Matching Analysis - Kazuaki Kuwabara; Shinya Matsuda; Koichi Benjamin Ishikawa; Hiromasa Horiguchi; Kenji Fujimori (Gastroenterology Research and Practice)
The safety of laparoscopic cholecystectomy (LC) in patients ≥65 years of age requires further investigation of postoperative outcomes before it becomes more widely accepted as a safe technique. The advantages of using LC versus open cholecystectomy (OC) in elderly patients were analyzed using propensity score matching. The demographics, cholecystitis severity, comorbidities, complications, and admission and discharge Barthel Index (BI) scores of patients with benign gallbladder diseases were analyzed. Outcomes were analyzed by age, length of stay (LOS), total charges (TCs), BI improvement, and postoperative complications. OC, which was indicated in severe disease cases, increased hospital resource use and caused more complications than LC, but did not improve BI. Advanced age and OC resulted in greater LOS and TCs and was the best indicator of BI deterioration. Whenever possible, surgeons should use LC in elderly patients to minimize postoperative complications and allow them to regain a good quality of life.